A Wolf in Sheep's Clothing: Exploring the Relationship Between Leader Humility and Unethical Behavior. (September 2022) - K. B, Darren; Lowe, Kevin B.; Bahmannia, Somayeh; Cui, Lin; Chen, Zhen Xiong
Prior research on the effects of leader humility implies that the more humility the leader exhibits, the greater the positive effect on recipients (e.g., followers and teams). However, little or no attention has so far been paid to the effects on the actors (e.g., leaders), who espouse humble behavior. In response to recent calls to theorize and examine how humility impacts these actors, this research draws on moral licensing theory, adopting an actor-centric approach to examine the mechanisms through which leader humility can lead to unethical behavior, such as unethical behavior for an organization (pseudobeneficial) and unethical behavior toward the organization (detrimental). Ultimately, we propose leader relational accountability as a moderator to mitigate the moral licensing effect of humble leaders. Results from a survey study provide support for the proposed hypotheses.